2019
DOI: 10.1177/2054358119838836
|View full text |Cite
|
Sign up to set email alerts
|

A Holistic Approach to Risk for Early Kidney Injury in Indigenous Youth With Type 2 Diabetes: A Proof of Concept Paper From the iCARE Cohort

Abstract: Background: Indigenous youth with type 2 diabetes (T2D) are disproportionately affected by early onset albuminuria and are at high risk of kidney failure in early adulthood. Traditional biological approaches have failed to fully explain the renal morbidity seen in this population. The improving renal Complications in Adolescents with type 2 diabetes through REsearch cohort (iCARE) study was therefore designed in collaboration with patients, to more holistically evaluate risk factors for renal morbidity. We hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
51
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(51 citation statements)
references
References 35 publications
0
51
0
Order By: Relevance
“…Forty-six studies reported hypertension prevalence ( Table 1 ). 4 , 15 , 17 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 The reported age at diagnosis of type 2 diabetes ranged from 7.1 to 20.0 years, 46 , 47 , 49 , 72 and the duration of diabetes ranged from inclusion at diagnosis 40 , 41 , 43 , 51 , 52 ,…”
Section: Resultsmentioning
confidence: 99%
“…Forty-six studies reported hypertension prevalence ( Table 1 ). 4 , 15 , 17 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 The reported age at diagnosis of type 2 diabetes ranged from 7.1 to 20.0 years, 46 , 47 , 49 , 72 and the duration of diabetes ranged from inclusion at diagnosis 40 , 41 , 43 , 51 , 52 ,…”
Section: Resultsmentioning
confidence: 99%
“…The kidney complications associated with youth onset T2D start earlier 1‐4 and progress more rapidly compared to type 1 and older onset type 2 populations 5,6 . Risk factors for progression have been evaluated in a few large cohorts such as the TODAY, 28,29 and SEARCH 30 studies and our own Canadian cohort 17 .…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the association between hypertension and albuminuria has not been consistent. Additional biopsychosocial risk factors 1 are emerging as important additional risk factors potentially linked to inflammatory pathways. Biopsy studies have shown that glomerular hypertrophy and focal glomerulosclerosis are important early histologic lesions in youth with T2D and albuminuria 31 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations